CORAK PENAFSIRAN M. QURAISH SHIHAB DALAM TAFSIR AL-MISBAH - Atik Wartini (State Institute of Islamic Studies (IAIN) Palu, 2014)
This article examines the patterns of M. Quraish Shihab’s interpretation in his work Tafsir Al-Misbah. From the beginning it appears that Tafsir al-Misbah uses multidipliner approach in assessing and interpreting the Koran. So that, it is can be concluded that M. Quraish Shihab is subjectivist position. It can be seen from his styles of interpretation often strengthened by historical data as the data interpretation or sometimes data cited from other holy scriptures such as Gospel and the Book of the Law. The later is cited to use as a comparison in order to strengthen his interpretation argument over the verses of Qur'an . Nowadays, these types of interpretation effort are quite influential in understanding the Qur'an. although the progression of the new interpretation is measured based on the ability of the developing community.Kata Kunci: Corak, quasi-Obyektifis Tradisionalis, Obyektifis, quasi Obyektifis Modernis